A Relationship Model between Top Management Team Cognitive Heterogeneity and Strategic Decision Quality and Its Implications for Sustainability - Qiannan Wang; Yuhui Ge; Cuihua Hu (Complexity)
To achieve sustainable development, a top management team (TMT) and the quality of its strategic decisions on sustainability are critical. This paper builds a relationship model between top management team (TMT) cognitive heterogeneity and the quality of strategic decisions. This research is important because TMT cognitive heterogeneity can comport decision-making schemes with complex and changing environments. Specifically, this paper explores the intermediary role of the team fusion process composed of different shareholders’ agents in integrating TMT heterogeneous cognition to improve the quality of strategic decisions. It adopts the upper echelon theory, which proposes that decision-makers have limited rationality and face difficulty in collecting and analyzing information in complex and changing environments. A questionnaire survey of 107 Chinese enterprises was conducted. Through the research framework of “cognitive heterogeneity–team fusion–strategic decision quality,” this paper constructs a moderated mediator model with entrepreneurial spirit as the moderating variable. Based on statistical analysis, the following results and contributions are obtained. First, TMT cognitive heterogeneity positively affected strategic decision quality. Second, two dimensions of team fusion—information integration and emotional fusion—mediated the relationship between TMT cognitive heterogeneity and strategic decision quality. Third, entrepreneurial spirit positively moderated the relationship between information integration and strategic decision quality, as well as the relationship between emotional fusion and strategic decision quality. The implications of our results related to sustainability are also discussed.